The effectiveness and safety of acupuncture combined with medication in the treatment of perimenopausal insomnia: a systematic review and meta-analysis - Jiang, Shengwen; Zhang, Yuan; Sun, Yingzhe (Frontiers in Neurology, 2025)
IntroductionThe aim of this study is to evaluate the effectiveness and safety of the combination therapy of acupuncture and medication in the treatment of perimenopausal insomnia (PMI). This research seeks to provide scientific evidence for clinical practice, optimize treatment protocols, and enhance the sleep quality and overall quality of life for women experiencing perimenopausal insomnia.Methods and analysisA comprehensive search was conducted across 8 databases, including the China National Knowledge Infrastructure (CNKI), Wanfang Academic Journal Full-text Database (Wanfang), Chongqing VIP Database (CQVIP), China Biology Medicine Disc (CBM), PubMed, Web of Science, Excerpta Medica Database (EMBASE), and Cochrane Library, from their establishment to July 1, 2024. Outcome measures were analyzed using Review Manager 5.4 and Stata 15.0 software. The included randomized controlled trials (RCTs) involved 1,187 patients with perimenopausal sleep disorders (596 in the experimental group and 591 in the control group). The analysis indicated that compared to Western medication alone, the combination therapy showed better efficacy [risk ratio (RR) = 1.24, 95% confidence interval (CI) (1.17, 1.31), p < 0.00001] and safety [RR = 0.31, 95%CI (0.18, 0.53), p < 0.0001]. It also demonstrated more significant improvements in Pittsburgh Sleep Quality Index (PSQI) [mean difference (MD) = −2.77, 95%CI (−4.11, −1.43), p < 0.0001], Hamilton Anxiety Rating Scale (HAMA) scores [MD = −3.45, 95%CI (−3.94, −2.97), p < 0.00001], Kupperman Menopausal Index (KMI) [MD = −1.46, 95%CI (−2.23, −0.70), p = 0.0002], Traditional Chinese Medicine Syndromes (TCMS) scores [MD = −2.45, 95%CI (−3.85, −1.04), p = 0.0006], and hormone levels, including Luteinizing Hormone (LH) [MD = −4.17, 95%CI (−7.42, −0.93), p = 0.01], Follicle-Stimulating Hormone (FSH) [MD = −10.50, 95%CI (−14.80, −6.20), p < 0.00001], and Estradiol (E2) [MD = 12.15, 95%CI (6.79, 17.51), p < 0.00001].DiscussionThe combination therapy demonstrates great efficacy and safety for PMI patients, representing an innovative integrative alternative treatment with high clinical application value.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024564357, PROSPERO CRD42024564357.